Comparison of Sevoflurane and Isoflurane for Myocardial Protection During Coronary Artery Bypass Surgery in a Tertiary Care Center in Nepal - Bastola, Priska; Pradhan, Bishwas; Basnet, Madindra (Journal of Institute of Medicine Nepal, 2019)
Introduction: Myocardial protection during Coronary Artery Bypass Graft (CABG) has always been an area of concern so we aimed to evaluate the level of release of Creatine Phosphokinase (CPK-MB) and Troponin I (cTnI) at various time intervals in the first 24 hours after on pump CABG in patients receiving either Sevoflurane or Isoflurane. Furthermore clinically relevant patient outcomes were also evaluated in patients undergoing on pump coronaryartery bypass grafting. Methods: This was a prospective randomized trial in patients undergoing on pump coronary artery bypass graft surgery, which was conducted from January 2016 till June 2017. A total of 105 patients were enrolled out of which there were 53 in Isoflurane and 52 in Sevoflurane group who received the respective volatile anesthetic agents throughout the surgery except during bypass at 1-1.5 MAC. The primary outcome was comparison of the CPK MB and cTnI levels at 0 hr, 6 hr, 12 hr and 24 hr after surgery from baseline, whereas the secondary outcomes were duration of intensive care unit stay, usage of vasopressors and inotropes, renal dysfunction, stroke. Results: No significant difference in CPK MB and cTnI levels at all time intervals in both the groups, the other secondary outcome parameters were comparable. Conclusion: The study found no difference in the cardiac markers between the two anesthetics. Based on the data, Sevofluraneand Isoflurane might be used equivalently in patients undergoing coronary artery bypass graft surgery with extracorporeal circulation without any difference in their myocardial protection function.